Different Tactics of Synthesized Zinc Oxide Nanoparticles, Homeostasis Ions, and Phytohormones as Regulators and Adaptatively Parameters to Alleviate the Adverse Effects of Salinity Stress on Plants - Mostafa Ahmed; Kincső Decsi; Zoltán Tóth (Life, 2022)
A major abiotic barrier to crop yield and profitability is salt stress, which is most prevalent in arid and semi-arid locations worldwide. Salinity tolerance is complicated and multifaceted, including a variety of mechanisms, and to adapt to salt stress, plants have constructed a network of biological and molecular processes. An expanding field of agricultural research that combines physiological measures with molecular techniques has sought to better understand how plants deploy tolerance to salinity at various levels. As the first line of defense against oxidative damage brought on by salt stress, host plants synthesize and accumulate several osmoprotectants. They (osmoprotectants) and other phytohormones were shown to serve a variety of protective roles for salt stress tolerance. Intrinsic root growth inhibition, which could be a protection mechanism under salty conditions, may be dependent on phytohormone-mediated salt signaling pathways. This article may also make it easier for scientists to determine the precise molecular processes underlying the ZnO-NPs-based salinity tolerance response for some plants. ZnO-NPs are considered to improve plant growth and photosynthetic rates while also positively regulating salt tolerance. When plants are under osmotic stress, their administration to zinc nanoparticles may also affect the activity of antioxidant enzymes. So, ZnO-NPs could be a promising method, side by side with the released osmoprotectants and phytohormones, to relieve salt stress in plants.